Effects of Graphene Content on Microstructure and Properties of Sintered Aluminum Materials - SHANG Xin - wen, CUI Zhi - yong (Cailiao Baohu)
In order to provide theoretical basis for manufacturing graphene aluminum products that meent specific conditions, graphene aluminum materials were prepared by spark plasma sintering process. The microstructure, mechanical properties and physical properties of graphene aluminum materials were studied by means of SEM, TEM, electronic universal testing machine, conductivity meter and other equipment. Results showed that the nickel - coated graphene could be uniformly dispersed in pure aluminum by ultrasonic dispersion and mechanical stirring. As the content of nickel - plated graphene increased from 0 to 0.87% (mass fraction), the tensile strength, hardness, conductivity and thermal conductivity of graphene aluminum materials were significantly improved. When the content of nickel - plated graphene was 0.87%, the tensile strength of the graphene aluminum material reached 194 MPa and its hardness was 52 HB, which were 168% and 23% higher than those of the pure aluminum discharge plasma sintered sample, respectively. The conductivity of graphene aluminum material reached 48.5% IACS, and the thermal conductivity was 193.7 W/(K·m).